2018
DOI: 10.11606/s1518-8787.2018052000525
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of socioeconomic gradients in the development of children aged 0–3 years in Fortaleza, Northeastern Brazil

Abstract: OBJECTIVETo identify the socioeconomic gradients in the measures of development and well-being of children under three years of age in Fortaleza, Northeastern Brazil.METHODSWe compiled information using a socioeconomic survey instrument, collecting anthropometric measurements, observing the home environment, and applying the Denver Test II to 2,755 children aged between zero and 28 months who are potential beneficiaries of the Cresça com Seu Filho program in Fortaleza. These children were randomly selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
5
Order By: Relevance
“…Earlier Kraków studies on the socio-demographic determinants of nutritional behaviour among preschool children revealed relationships between the children's eating behaviours and the level of parents' education and family income [19]. A Brazilian study also confirmed the predictive importance of socio-economic factors on the development of indicators regarding nutritional status among children aged 0-3, with an indication of more favourable rates for children of mothers with higher socio-economic status [2]. Diversity in the nutritional value of the diet depending on living environment has been described among Mexican preschool children, with an indication of more favourable results among urban children than in rural areas [15].…”
Section: 7% Energy)mentioning
confidence: 77%
“…Earlier Kraków studies on the socio-demographic determinants of nutritional behaviour among preschool children revealed relationships between the children's eating behaviours and the level of parents' education and family income [19]. A Brazilian study also confirmed the predictive importance of socio-economic factors on the development of indicators regarding nutritional status among children aged 0-3, with an indication of more favourable rates for children of mothers with higher socio-economic status [2]. Diversity in the nutritional value of the diet depending on living environment has been described among Mexican preschool children, with an indication of more favourable results among urban children than in rural areas [15].…”
Section: 7% Energy)mentioning
confidence: 77%
“…Em uma parcela representativa da amostra, foi constatada baixa escolaridade materna (RP=1,26; 1,08-1,47). Apesar de muitos lares brasileiros terem os pais como responsáveis pelo equilíbrio financeiro da residência, em grande parte deles, as mães são encarregadas de manter o núcleo familiar, como provedoras e incentivadoras dos filhos na continuidade dos estudos 35 . Muitos adolescentes conciliam o estudo com o trabalho precoce, porém a dedicação exclusiva a atividades escolares demonstra-se favorável a resultados que se traduzem em um futuro profissional possivelmente mais próspero 4,36 .…”
Section: Discussionunclassified
“…Estes resultados estão de acordo com outros encontrados na literatura (ANDERSON et al, 2003, p. 37-38;BOO;MATEUS;DURYEA, 2018, p. 8;GERZSON et al, 2016, p. 182;RIZZOLI-CÓRDOBA et al, 2017, p. 105), pois o desenvolvimento na primeira infância é influenciado por características dos ambientes nos quais a criança está inserida. Assim programas que investem na qualidade educacional vão trazer impactos positivos no desenvolvimento de crianças, principalmente daquelas economicamente desfavorecidas.…”
Section: Discussionunclassified